Impact of Cybersecurity Threats on Emerging Markets’ Integration into Global Trade Networks - Narsina, Deekshith (American Journal of Trade and Policy, 2022)
This paper explores how cybersecurity concerns affect developing market integration into global trade networks, concentrating on digital market vulnerabilities. The research seeks to identify developing economies’ biggest cybersecurity dangers, examine their effects on global commerce, and suggest resilience methods. Cybersecurity threats and their consequences on trade systems are examined via secondary data-based reviews of literature, reports, and case studies. Due to obsolete infrastructure, inadequate regulatory frameworks, and a cybersecurity skills gap, developing countries are susceptible to cyberattacks. Besides disrupting commerce, these vulnerabilities also damage investor confidence and global supply systems. The report stresses the necessity of improved digital infrastructure, cybersecurity policies, and local professional capacity development. It emphasizes international collaboration and public-private partnerships to strengthen cybersecurity resilience. Policy implications include that developing market countries must emphasize cybersecurity in trade policies and comply with global norms to promote safe and sustainable global commerce. By tackling these issues, emerging economies may boost trade competitiveness and global economic stability.